2012
DOI: 10.1186/1471-2474-13-148
|View full text |Cite
|
Sign up to set email alerts
|

Hypermobility of the first metatarsal bone in patients with Rheumatoid arthritis treated by lapidus procedure

Abstract: BackgroundFoot deformities and related problems of the forefoot are very common in patients with rheumatoid arthritis. The laxity of the medial cuneometatarsal joint and its synovitis are important factors in the development of forefoot deformity. The impaired joint causes the first metatarsal bone to become unstable in the frontal and sagittal planes. In this retrospective study we evaluated data of patients with rheumatoid arthritis who underwent Lapidus procedure. We evaluated the role of the instability in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 31 publications
2
16
0
1
Order By: Relevance
“…They achieved good to excellent pain relief in 80 % of patients. These results were echoed by Popleka et al in their study [56]. They concluded that the Lapidus procedure may be useful as a preventive surgery.…”
Section: Surgical Managementsupporting
confidence: 68%
“…They achieved good to excellent pain relief in 80 % of patients. These results were echoed by Popleka et al in their study [56]. They concluded that the Lapidus procedure may be useful as a preventive surgery.…”
Section: Surgical Managementsupporting
confidence: 68%
“…In case of moderate to severe HV and/or insufficiency of the first ray, modified Lapidus procedure is known to be associated with good clinical outcome (Faber et al, 2013;McInnes and Bouche, 2001;Popelka et al, 2012;Toolan, 2007;Willegger et al, 2015) due to efficient correction of the deformity and stabilization of the first ray (Avino et al, 2008;Galli et al, 2015;King et al, 2014;Popelka et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The rate of union in our series was compared to similar studies in the published literature using the two-population probability test, or Z-test. 2,4,[11][12][13][14][15][16][17][18][19] To allow for the use of the two-population probability test, only case series were used where the total number of feet and non-unions were reported. The significance level was set at p<0.05.…”
Section: Statisticsmentioning
confidence: 99%
“…Fixation in these studies were mainly solid AO screws, or locked plates with or without lag screws. 2,4,[10][11][12][13][14][15][16][17][18][19]…”
Section: Union Ratesmentioning
confidence: 99%